A Switch in the Hydrophobic/Hydrophilic Gas‐Adsorption Character of Prussian Blue Analogues: An Affinity Control for Smart Gas Sorption. Issue 2 (11th December 2018) - Boudjema, Lotfi; Long, Jérôme; Salles, Fabrice; Larionova, Joulia; Guari, Yannick; Trens, Philippe
Abstract: Porous coordination polymers are molecule‐based materials presenting a high degree of tunability, which offer many advantages for targeted applications over conventional inorganic materials. This work demonstrates that the hydrophilic/hydrophobic character of Prussian blue analogues having a lipophilic feature may be tuned to optimize the gas adsorption properties. The role of the coordinatively unsaturated metal sites is emphasized through a combination of theoretical and experimental study of water, ethanol, and n ‐hexane adsorption. Abstract : Chemically unsaturated sites : A hydrophobic Prussian Blue analogue can be turned highly hydrophilic by pre‐adsorbing water molecules on the chemically unsaturated sites of the material. The hydrophilic/hydrophobic balance of this PBA can be finely tuned depending on the application targeted (see scheme).